2005
DOI: 10.1002/cncr.20988
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed in anaplastic thyroid carcinoma‐1 (OEATC‐1) as a novel gene responsible for anaplastic thyroid carcinoma

Abstract: BACKGROUNDAnaplastic thyroid carcinoma (ATC) is one of the most fulminant human malignancies. However, the molecular carcinogenic mechanisms of ATC are understood poorly. Recently, the authors performed a cyclic DNA (cDNA) microarray analysis with 11 anaplastic thyroid carcinoma cell lines (ACLs) and discovered several novel responsible genes for ACLs and ATC. From the extended list, they focused on hypothetical and anonymous genes and investigated a novel gene, named the overexpressed in anaplastic thyroid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 11 publications
(9 reference statements)
2
56
1
Order By: Relevance
“…Interestingly, ATF3 and p15 PAF expressions peaked at 2 h after irradiation, suggesting a coordinated regulation with the presence of CPDs (Figure 3). To assess the direct contribution of both genes in the DNA repair process, HaCaT cells were rendered deficient by the transfection of siATF3 and sip15 PAF , 13 or siLuc as a control, 24 h after transfection, DNA damage was induced by irradiation with a single low dose of UVC (5 J/m 2 ). After 24 h of recovery, the presence of CPD-positive cells was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, ATF3 and p15 PAF expressions peaked at 2 h after irradiation, suggesting a coordinated regulation with the presence of CPDs (Figure 3). To assess the direct contribution of both genes in the DNA repair process, HaCaT cells were rendered deficient by the transfection of siATF3 and sip15 PAF , 13 or siLuc as a control, 24 h after transfection, DNA damage was induced by irradiation with a single low dose of UVC (5 J/m 2 ). After 24 h of recovery, the presence of CPD-positive cells was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…5 During development, KIAA0101 protein expression is highly restricted in a spatiotemporal manner in mouse embryos, whereas it shows aberrant expression in various cancers, such as breast, uterine cervix, brain, kidney, hepatic, lung, esophageal, and colon cancers. 6,7 However, not all of the clinical studies on KIAA0101 have supported the conclusion that KIAA0101 functions as an oncogene in tumor progression, 6,8 perhaps because some functions of the KIAA0101 protein are related to DNA repair; alteration of the latter activity is usually associated with tumorigenesis, but gaining functions of DNA repair will promote tumor progression and resistance to cisplatin-based chemotherapy. 9 During cancer development, the lack of KIAA0101 activity alters chromosome instability, for example, changes in gene copy number are noted.…”
mentioning
confidence: 99%
“…Only 27 PDTC have been evaluated by comparative genomic hybridisation (CGH) analysis, and as far as we are aware, there are no microarray studies on this entity (Wreesmann et al, 2002;Rodrigues et al, 2004). In ATC, it was demonstrated that TP53 (Wynford- Thomas, 1997) and b-catenin (Garcia-Rostan et al, 1999) mutations as well as the overexpression of OEATC1 (Mizutani et al, 2005) and AURKB (Sorrentino et al, 2005) were associated with ATC phenotype. These genes were demonstrated to be key effectors in anaplastic transformation, being responsible for evasion to apoptosis, enhanced tumour growth and replicative potential.…”
mentioning
confidence: 99%